ROE, DER, DAN CR PADA NILAI PERUSAHAAN PERBANKAN DI BEI (2021-2023) - Nurhalisa, Mutiara; Tyasarila, Sheiny Raka; Octavia, Ayu Nurafni (Fakultas Ekonomi, Bisnis dan Humaniora, 2025)
In the increasingly competitive world of business, a company's value can determine its direction and performance. This value can influence investor perceptions when assessing a company before investing. This study aims to examine the effect of Return on Equity (ROE), Debt to Equity Ratio (DER), and Current Ratio (CR) on the Firm Value of banking sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. The population in this study consists of banking sector companies listed on the IDX during that period, totaling 47 companies. The sampling technique used is purposive sampling, where samples are selected based on certain criteria, resulting in a sample of 46 companies. The data analysis technique employed is multiple linear regression analysis. The study's results indicate that ROE has a significant positive effect on Firm Value, DER has a significant negative effect on Firm Value, and CR has a significant positive effect on Firm Value. The coefficient of determination, or R Square, is only 42.3%, meaning that the independent variables explain only 42.3% of the variance in the dependent variable, suggesting the need to investigate additional variables